Organization of polythiophenes at ultrathin films mixed with stearic acid investigated with polarization-modulation infrared reflection–absorption spectroscopy - Silva, Edilene Assunção da [UNESP]; Caseli, Luciano; Olivati, Clarissa de Almeida [UNESP] (Elsevier, 2017)
In this present work, the polymers poly(3-alkylthiophene)s, regioregular poly(3-butylthiophene), poly(3-hexylthiophene) and poly(3-octylthiophene) were spread at the air-water interface to form Langmuir monolayers. They formed stable films by mixing them with Stearic Acid (SA), as confirmed with surface pressure-area isotherms and polarization-modulation infrared reflection–absorption spectroscopy (PM-IRRAS). The floating monolayers were transferred from the liquid interface to solid supports by using the Langmuir-Blodgett (LB) and Langmuir-Schaeffer (LS) techniques, and characterized with PM-IRRAS. Surface pressure-area isotherms showed that SA monolayers are expanded upon polymer incorporation altering the rheological properties of the monolayer since the monolayer became less elastic at higher pressures and presented first-order transitions at lower pressures. PM-IRRAS showed that the organization of the films is affected at the molecular level depending on the chemical structure of the polymer chosen. Among the polymers analysed, the poly(3-butylthiophene) shows a more irregular conformational behaviour depending on the amount of stearic acid. The conformation of the films when transferred to solid support changes and is dependent on the type of deposition (LB or LS). The importance of this paper relies on the fact that SA can be employed to help the formation of stable floating monolayers of these polythiophenes at the air-water interface, and the successful transfer to solid supports may provide nanostructured films with a high control of their molecular properties, which may enable a molecular architecture to be applied as electronic devices of interest.
Keywords: Langmuir-Blodgett films; Langmuir-Schaefer films; Monolayers; PM-IRRAS; Polyalkylthiophenes; Stearic acid